Monodispersed Ru nanoparticles functionalized graphene nanosheets as efficient cathode catalysts for O2-assisted Li-CO2 battery - Wang, Liangjun (2021)
In Li-CO2 battery, due to the highly insulating nature of the discharge product of Li2CO3, the battery needs to be charged at a high charge overpotential, leading to severe cathode and electrolyte instability and hence poor battery cycle performance. Developing efficient cathode catalysts to effectively reduce the charge overpotential represents one of key challenges to realize practical Li-CO2 batteries. Here, we report the use of monodispersed Ru nanoparticles functionalized graphene nanosheets as cathode catalysts in Li-CO2 battery to significantly lower the charge overpotential for the electrochemical decomposition of Li2CO3. In our battery, a low charge voltage of 4.02 V, a high Coulomb efficiency of 89.2%, and a good cycle stability (67 cycles at a 500 mA h/g limited capacity) are achieved. It is also found that O2 plays an essential role in the discharge process of the rechargeable Li-CO2 battery. Under the pure CO2 environment, Li-CO2 battery exhibits negligible discharge capacity; however, after introducing 2% O2 (volume ratio) into CO2, the O2-assisted Li-CO2 battery can deliver a high capacity of 4742 mA h/g. Through an in situ quantitative differential electrochemical mass spectrometry investigation, the final discharge product Li2CO3 is proposed to form via the reaction 4Li+ + 2CO2 + O2 + 4e- → 2Li2CO3. Our results validate the essential role of O2 and can help deepen the understanding of the discharge and charge reaction mechanisms of the Li-CO2 battery.